Psychology and work today - Carrie, A Bulger; Schultz,Duane P; Schultz,Sydney Ellen (New York Routledge Taylore and Francis Group, 2023)
Psychology and Work Today, 11th Edition is an exciting update of a well-loved textbook that introduces industrial and organizational psychology, explaining how industrial-organizational psychologists make work and working better. This accessible and informative text explains how industrial-organizational psychologists help organizations hire the best people by designing tests and interviews that uncover the skills and abilities of applicants, make work better by removing or reducing safety issues and sources of stress so that personnel are motivated and able to perform to their abilities, and work with managers and leaders to be more effective at leading others. This book also describes how industrial-organizational psychologists work with organizations to embrace diversity in the workforce and celebrate the strengths that employees from many backgrounds bring to organizations. In addition, this text includes how psychologists help organizations to design the physical work environment to best suit employees, while other psychologists help organizations to market their products and services to consumers.